Large area, broadband and highly sensitive photodetector based on ZnO-WS2/Si heterojunction. (August 2020) - Patel, Meswa; Pataniya, Pratik M.; Patel, Vikas; Sumesh, C.K.; Late, Dattatray J.
Highlights: WS2 -ZnO Nanocomposite was synthesized by microwave assisted synthesis technique. Liquid phase exfoliated WS2 Nanosheets have band gap of 1.95 eV. Device shows short response time and significantly enhanced detector parameter. Device exhibits reproducible and stable photoresponse in broad spectral region. Abstract: Recently, the development of opto-electronics that is integrated with ultra-broad spectral range has attracted tremendous attention. The fabricated devices should have high photoresponsivity, specific detectivity and fast switching. Herein, efforts have been applied to synthesis WS2 -ZnO (WZO) heterostructure using high-yield microwave assisted synthesis and to fabricate large area WZO/Si heterojunction photodiode. The efforts have also been applied to find number of atomic layers in WS2 nanosheets using Raman spectroscopy and absorption spectroscopy. The WZO/Si photodiode exhibits current rectifying behaviour (with rectification ratio 155 at 1.5 V), self-powered photodetection, improved photoresponsivity and detectivity in broad in spectral range 390–1080 nm and higher electrical stability in dark and under illumination. Present findings advocate the huge development in facile fabrication of high-performance opto-electronics over previously reported devices.